Combination of Melatonin and Zoledronic Acid Suppressed the Giant Cell Tumor of Bone in vitro and in vivo - Wang, Xudong; Su, Peiqiang; Kang, Yan; Xu, Caixia; Qiu, Jincheng; Wu, Jinna; Sheng, Puyi; Huang, Dongsheng; Zhang, Ziji (Frontiers in Cell and Developmental Biology, 2021)
Melatonin (Mlt) confers potential antitumor effects in various types of cancer. However, to the best of our knowledge, the role of Mlt in the giant cell tumor of bone (GCTB) remains unknown. Moreover, further research is required to assess whether Mlt can enhance the therapeutic effect of zoledronic acid (Zol), a commonly used anti-GCTB drug. In this research, we investigated the effects of Mlt, Zol, and the combination of these two drugs on GCTB cells’ characteristics, including cell proliferation, apoptosis, osteogenic differentiation, migration, and invasion. The cell counting kit-8 assay, colony formation assay, terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay, alkaline phosphatase staining, alizarin red staining, scratch wound healing assay, and transwell experiment were performed, respectively. Our results showed that Mlt could effectively inhibit the proliferation, migration, and invasion of GCTB cells, as well as promote the apoptosis and osteogenic differentiation of tumor cells. Of note, a stronger antitumor effect was observed when Mlt was combined with Zol treatment. This therapeutic effect might be achieved by inhibiting the activation of both the Hippo and NF-κB pathways. In conclusion, our study suggests that Mlt can be a new treatment for GCTB, which could further enhance the antitumor effect of Zol.